Key Aspects of Macroprudential Policy : Background Paper. (Policy Papers; Policy Paper, 2013)
The countercyclical capital buffer (CCB) was proposed by the Basel committee to increase the resilience of the banking sector to negative shocks. The interactions between banking sector losses and the real economy highlight the importance of building a capital buffer in periods when systemic risks are rising. Basel III introduces a framework for a time-varying capital buffer on top of the minimum capital requirement and another time-invariant buffer (the conservation buffer). The CCB aims to make banks more resilient against imbalances in credit markets and thereby enhance medium-term prospects of the economy-in good times when system-wide risks are growing, the regulators could impose the CCB which would help the banks to withstand losses in bad times.